The rise of the eSports industry in Malaysia / Dr. Hazira Mohd Nasir ... [et al.]. - Mohd Nasir, Hazira; Mohd Zaid, Noor Azila; Musa, Aini Hayati; Mohd Beta, Raja Mayang Delima (Universiti Teknologi MARA, Negeri Sembilan, 2024)
“The rise of eSports in Malaysia marks a new era in our digital and cultural landscape.” The recent surge in electronic sports, or eSports, globally has transformed gaming into a dynamic new industry, merging technology, entertainment, and sport in unprecedented ways. This exciting trend has taken off in earnest across Malaysia as it has elsewhere. This article delves into the development of the eSports industry in Malaysia, exploring both its challenges and opportunities. The Development of the eSports Industry in Malaysia The cultural phenomenon of eSports has its roots in the late 1970s and early 1980s, but competitive gaming reached a turning point in the early 21st century with faster internet connections and gaming technologies.